Ecological, taxonomic and distributional aspects of benthic cyanobacteria in five streams of central Mexico - Cartajena Alcántara, Mariana Guadalupe; Carmona Jiménez, Javier; Perona Urizar, Elvira (Instituto de Ecología, A.C., 2020)
Background and Aims: Cyanobacteria are oxyphototrophic prokariotic algae present in great variety of habitats and they are important components of the benthic communities in many continental and marine environments. In Mexico, their diversity in streams is less known; therefore, this study contributes to phycofloristic knowledge in five streams of the central region of Mexico. Descriptions and illustrations, estimations of their diversity, an analysis of the relationships between growth forms and microenvironmental factors are included, and the validity of their morphological and ecological characterization in the delimitation of the species found is discussed. Methods: Sampling was carried out in dry and rainy seasons in two siliceous streams and three calcareous streams of central Mexico. Water temperature, specific conductivity and pH were recorded, major ions (Ca2+, Mg2+, K+, Na+, Si-SiO2, HCO3-, Cl-, SO43-) and nutrients (NH4+, NO2-, NO32-, PO43-) were analyzed, the diversity was estimated of the cyanobacteria registered with the Shannon-Weaver index, and their habitats and microhabitats were described. Taxonomic identification was carried out with specialized literature. Key results: Four associations and nine species belonging to three orders, seven families and seven genera were identified. Two groups were distinguished: one formed by Nostoc parmelioides-Coleodesmium wrangelii, Phormidium lividum-Leptolyngbya truncata in siliceous and mountain streams, and one composed by Schizothrix mexicana-Phormidium subfuscum, Homoeothrix juliana-Heteroleibleinia fontana and Nostoc verrucosum in calcareous, warm streams. Two ecological distribution patterns were recognized: 1) the Nostocales species present in stressful conditions of light and current velocity and 2) the taxa of Oscillatoriales and Synechoccales registered in sites with mean values of light and water flow. Conclusions: Morphological and ecological characterization of cyanobacterial species contributes to their phycofloristic knowledge and the base for future research on taxonomy, systematics and sustainable use of algal resources.